Trends in treatment patterns and costs of care among patients with advanced stage cervical cancer - Musa, Fernanda B.; Brouwer, Elizabeth; Ting, Jie; Schwartz, Naomi R.M.; Surinach, Andy; Bloudek, Lisa; Ramsey, Scott D. (Gynecologic oncology, 2022)
Current treatments for recurrent or metastatic cervical cancer (r/mCC) do not offer satisfactory clinical benefits, with most patients progressing beyond first-line (1L) treatment. With new treatments under investigation, understanding current treatment patterns, the impact of newly approved therapies, and total costs of care for r/mCC are important. A retrospective analysis of a US commercial insurance claims database to identify adult patients with r/mCC between 2015 and Q1–2020; defining 1L treatment as the first administration of systemic treatment without concomitant chemoradiation or surgery. Patient characteristics, treatment regimens, duration of therapy, and total costs of care were evaluated for each line of therapy. 1323 women initiated 1L treatment for r/mCC (mean age, 56.1 years; mean follow-up, 16.5 months). One-third (n = 438) had evidence of second-line (2L) treatment; of these, 129 (29%) had evidence of third-line (3L) treatment. No regimen represented a majority among 2L+ treatments. The 2018 approval of pembrolizumab led to increased 2L immunotherapy use (0% in 2015, 37% in 2019/Q1–2020). However, only a small proportion of patients stayed on immunotherapy for a prolonged period. Mean per-patient-per-month total costs of care during treatment were $47,387 (1L), $77,661 (2L), and $53,609 (3L), driven primarily by outpatient costs. No clear standard of care was observed in 2L+. Although immunotherapy is increasingly used in 2L+, only a small subset of patients stayed on immunotherapy for a prolonged period, suggesting a need for more therapeutic options. Better understanding of disease biology and the introduction of new therapies may address these unmet needs. •There is no clear standard of care observed in 2L+ r/mCC.•Immunotherapy use in 2L increased from 0% in 2015 to 37% in Q1 2020.•However, only a small proportion stayed on immunotherapy for a prolonged period.•Average costs per patient per month across lines ranged from $47,000 to $77,000.•Therapeutic options with differentiated modalities are needed for 2L+ patients.